The effects of the domestication on the behaviour of goose under intensive conditions - Molnár, Marcell; Bogenfürst, Ferenc; Molnár, Tamás; Almási, Anita (Acta Agraria Kaposváriensis, 2002)
In the intensive rearing techniques of goose the adequate keeping conditions needed for continuous production are provided independently of seasons. It is a totally new technology about which very small amount of information has been collected till now. The needs of geese under intensive conditions are almost unknown, so it is important to examine their behavior in the offered circumstances. Based on the these results factors of the rearing technology can be elaborated according to the characteristics of the species and the production, parallel to the well-being of the animals can be improved. Nowadays, when the rides of animal welfare tend to become more and more strict, importance of studies like this is evident. In our study the behavior of 8 Szentes Big White and 8 wild geese were compared to examine the effect of domestication. Based on our results it can be declared that the wild goose is more active in the rearing period than the domesticated form. It manifests in a higher ratio of the preening and playing, but the frequency of the feeding and drinking was also higher. The explanation of this phenomenon in case of feeding can be the stronger need for search of food, while the differences in the preening can be rooted in the inability of flying of the domesticated form. The social behaviour had a lower level by the domesticated goose because the domestication has a reducing effect on the aggression.